The Urgency of Religious Moderation amid Indonesia's Diversity - Salma Khoerunisa; Shahibah Yuliani (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: Indonesia's rich religious, ethnic, and cultural diversity is a source of pride but also presents challenges to social harmony. The rise of extremism and intolerance highlights the urgent need for a balanced and inclusive approach to religious life. Objective: This study aims to analyze the urgency of religious moderation within Indonesia's diverse society and to identify the potential consequences if such moderation is neglected. Method: A qualitative method was employed, using a library research approach to examine relevant literature, policy documents, and scholarly publications. Result: The findings indicate that without a moderate approach to religious life, the risks of social conflict and national disintegration increase significantly. Religious moderation has proven effective in reducing extremism, fostering interfaith dialogue, and strengthening the values of tolerance and unity within the framework of Pancasila and Bhinneka Tunggal Ika. Conclusion: Religious moderation plays a critical role as a middle path that can help mitigate the tensions arising from Indonesia's rich religious diversity. Religious moderation, deeply rooted in Cultural heritage, bridges differing religious practices and local wisdom. Contribution: The contribution of this research lies in offering a deeper conceptual understanding of the importance of religious moderation as a preventive strategy for maintaining national integration and as a foundation for inclusive educational and social policy development.